2021
DOI: 10.14569/ijacsa.2021.0120767
|View full text |Cite
|
Sign up to set email alerts
|

SIP-MBA: A Secure IoT Platform with Brokerless and Micro-service Architecture

Abstract: The Internet of Things is one of the most interesting technology trends today. Devices in the IoT network are often geared towards mobility and compact in size, thus having a rather weak hardware configuration. There are many light weight protocols, tailor-made suitable for limited processing power and low energy consumption, of which MQTT is the typical one. The current MQTT protocol supports three types of qualityof-service (QoS) and the user has to trade-off the security of the packet transmission by transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…One disadvantage of centralized storage in the above approaches is transparency [25]. To address this issue, Lam et al [26], [27] demonstrated the implementation of a micro services-oriented software architecture for middleware that collects, stores, and traces data in a centralized manner in order to provide data analysis. To apply these advantages, a centralized blood donation management solution has been proposed in [28].…”
Section: Related Workmentioning
confidence: 99%
“…One disadvantage of centralized storage in the above approaches is transparency [25]. To address this issue, Lam et al [26], [27] demonstrated the implementation of a micro services-oriented software architecture for middleware that collects, stores, and traces data in a centralized manner in order to provide data analysis. To apply these advantages, a centralized blood donation management solution has been proposed in [28].…”
Section: Related Workmentioning
confidence: 99%
“…One disadvantage of centralized storage in the above approaches is transparency [26], [27]. To address this issue, Lam et al [28], [29] demonstrated the implementation of a micro services-oriented software architecture for middleware that collects, stores, and traces data in a centralized manner in order to provide data analysis. However, for the specific requirement (e.g., blood donation w.r.t supply chain), we need a specific model to balance the demand (i.e., blood recipients) and supply (i.e., the time for the next round of donors).…”
Section: A Healthcare Systems Based On Blockchain Technologymentioning
confidence: 99%
“…For the cloud-based decentralized processing model, the centralized storage and processing of data from multiple sources often leads to data inconsistencies among the involved parties, thereby creating limited cooperation opportunities for stakeholders [9,10]. In addition, this model is flawed in providing traceability, reliability, operational transparency, security, and reliability features in processing [11,12]. On the other hand, a significant factor in the current epidemic problem is the ability to encourage non-face-to-face interaction (i.e., limit face-to-face meetings) to avoid transmission, which has presented a complicated issue for the community, the management of equipment, supplies, and medical waste.…”
Section: Introductionmentioning
confidence: 99%